UPAYA PENINGKATAN PROFESIONALISME GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ahmad Suyuthi (Al Hikmah: Jurnal Studi Keislaman, 2011)
low professionalism of teachers due to; there are many teachers who did not pursue his profession as a whole, the existence of private universities as teachers created who have graduated is regardless of its output later in the field, lack of motivation in improving teacher quality. Government efforts in enhancing the professionalism of them by the holding of the certification program. Another effort that teachers can do in enhancing professionalism in teaching Islamic lesson, such as; by increasing PAI; mastering of materials, managing the teaching-learning programs, classroom management, development of teaching methods, use of media technology and learning, to master the foundation of education, skilled in interacting with students by considering the objectives and student learning materials and conditions, also increasing the ability to evaluate student achievement. While efforts can be made from the school, such as; Provision of adequate facilities and infrastructure, responsibility and oversight, supervision and quality improvement and welfare of teachers.